Efficacy of Olive Leaf Extract Mouthwash on Clinical and Inflammatory Parameters of Gingival Inflammation in Relation to Chlorhexidine in Acute Gingivitis Serum Patients - Sabah Hasan , Liqa; Ibrahim Latif , Ismail; Hammed Mohammed, Shakir (Diyala Journal of Medicine, 2022)
Background: Oral and gum infections are mostly linked to poor oral hygiene. Chlorhexidine mouthwash, and teeth brushing, have been commonly recommended. There is many studies on the effectiveness of olive leaf extract (OLE) as herbal mouthwash, there is much guided on its competitive effect with chlorhexidine. Objective: To determine the clinical and inflammatory effects of olive leaf extract (OLE) as mouthwash in the treatment of acute gingivitis and compare its effect with 0.12% chlorhexidine mouthwash (CHX). Patients and Methods: A total of 60 subjects aged 18-35 years with acute gingivitis underwent scaling and polishing with oral hygiene instruction; 20 patients received 3% of (OLE) as mouthwash, 20 patients received of 0.12% of chlorhexidine mouthwash (CHX), and 20 patients received scaling and polishing only (SRP) without any mouthwash. Mouthwash was twice daily for 17 days. At the start of the study, clinical periodontal parameters (PI, GI and BOP) and blood samples were taken and after five weeks of treatment to estimate the levels of C-reactive protein (CRP), alkaline phosphatase (ALP) and total protein (TP). Results: After 5 weeks of periodontal treatment, there was a significant decrease in clinical periodontal parameters (P<0.01) and inflammatory markers (P<0.05) in the OLE and CHX and S&P alone groups. From periodontal treatment, there was no significant difference between the OLE and CHX groups with clinical periodontal parameters and inflammatory markers (P<0.05), although there was a significant difference between the OLE, CHX groups and the S&P alone group in terms of clinical periodontal parameters and inflammatory markers (P<0.05). Conclusion: Olive leaf extract (OLE) has been showed to be comparable to CHX aided in reducing gingivitis by decreasing clinical periodontal parameters and inflammatory chemical markers values such as CRP, ALP, and TP.